Effect of probiotics on children with autism spectrum disorders: a meta-analysis - Ping Zeng; Cheng-zhi Zhang; Zhi-xing Fan; Chao-jun Yang; Wan-yin Cai; Yi-fan Huang; Zu-jin Xiang; Jing-yi Wu; Jing Zhang; Jian Yang (BMC, 2024)
Abstract Background Researches have found that alteration of intestinal flora may be closely related to the development of autism spectrum disorder (ASD). However, whether probiotics supplementation has a protective effect on ASD remains controversial. This meta-analysis aimed to analyze the outcome of probiotics in the treatment of ASD children. Methods The Pubmed, Cochrane Library, Web of Science and Embase were searched until Sep 2022. Randomized controlled trials (RCTs) relevant to the probiotics and placebo treatment on ASD children were screened. Quality assessment of the included RCTs was evaluated by the Cochrane collaboration's tool. The primary outcomes were ASD assessment scales, including ABC (aberrant behavior checklist) and CBCL (child behavior checklist) for evaluating the behavior improvement, SRS (social responsiveness scale) for social assessment, DQ (developmental quotient) for physical and mental development and CGI-I (clinical global impression improvement) for overall improvement. The secondary outcome was total 6-GSI (gastrointestinal severity index). Results In total, 6 RCTs from 6 studies with 302 children were included in the systemic review. Total 6-GSI (MD=-0.59, 95%CI [-1.02,-0.17], P < 0.05) decreased significantly after oral administration of probiotics. Whereas, there was no statistical difference in ABC, CBCL, SRS, DQ and CGI-I between probiotics and placebo groups in ASD children. Conclusion Probiotics treatment could improve gastrointestinal symptoms, but there was no significant improvement in ASD.